Poor Sleep in Community-Dwelling Polysubstance Users: Association With Khat Dependence, Metacognition, and Socio-Demographic Factors - Manzar, Md Dilshad; Alghadir, Ahmad H.; Khan, Masood; Salahuddin, Mohammed; Hassen, Hamid Yimam; Almansour, Ahmed M.; Nureye, Dejen; Tekalign, Eyob; Shah, Showkat Ahmad; Pandi-Perumal, Seithikurippu R.; Bahammam, Ahmed S. (Frontiers in Psychiatry, 2022)
Purpose: Sleep disturbances and cognitive deficits are often associated with increased drug use. However, no study has addressed the relationship between sleep quality, substance dependence, and metacognitive deficit in polysubstance users. Methods: This was a cross-sectional study with a simple random sampling involving community-dwelling polysubstance users (n=326, age=18-43 years) in Mizan, Ethiopia. Participants completed a brief sleep questionnaire, severity of dependence on Khat (SDS-Khat), a brief meta-cognition questionnaire, and a Socio-demographic survey. Results: Majority (56.4%) of the polysubstance users had sleep disturbance. Chronic health conditions (AOR) = 2.52, 95% (CI)1.31-4.85), chronic conditions in the family (AOR) = 2.69, 95%(CI)1.40-5.20), Illiterate-primary level of educational status (AOR) = 2.40, 95%(CI)1.30-4.04), higher SDS-Khat score (AOR) = 1.39, 95%(CI)1.13-1.72), and lower meta-cognition score (AOR) = 0.90, 95%(CI)0.84-0.97) predicted poor sleep in the polysubstance users. Moreover, low metacognition score and high SDS score also predicted additional sleep disturbances like chronic sleep insufficiency, lethargy and restlessness after nighttime sleep, socio-occupational dysfunctions, and daytime disturbances in polysubstance users. Conclusion: Poor sleep, severe khat-dependence, metacognitive deficits are common in community polysubstance users. Moreover, poor sleep is associated with higher khat-dependence, lower metacognitive ability, lower educational status, and the presence of chronic conditions in polysubstance users or their families.